Comparison of Chromatogram Profiles of Red Ginger (Zingiber officinale var. rubrum Theilade) Rhizome Essential Oil Based on Differences in Growing Places - Styawan, Anita Agustina; Mustofa, Helmi; Kusumadewi, Awal Prichatin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Red ginger (Zingiber officinale var. rubrum Theilade) is a valuable raw material for the pharmaceutical, cosmetic, and food industries, primarily due to its rich essential oil content. This study investigated how cultivation location influences the chromatographic profile of Z. officinale var. rubrum essential oil. Samples were sourced from two distinct regions in Java, Indonesia: Magelang and Pacitan Regencies. Essential oils were isolated using water distillation, and their chemical compositions were subsequently analyzed via gas chromatography-mass spectrometry (GC-MS). A notable difference in essential oil yield was observed, with Magelang producing 0.1% and Pacitan yielding 0.08%. GC-MS analysis of the Magelang sample identified 16 compounds, prominently featuring E-citral (20.30%), Z-citral (11.31%), geraniol (10.34%), and camphene (8.91%). Conversely, the Pacitan sample contained 15 compounds, with E-citral (24.06%), Z-citral (13.93%), camphene (14.86%), and 1,8-cineole (7.86%) as its major constituents. A Mann-Whitney U test confirmed a statistically significant difference (p-value = 0.025 < 0.05) in the essential oil profiles between the two locations. These variations are likely attributable to diverse environmental factors, including soil composition, altitude, ambient temperature, and rhizome maturity. This research underscores the critical role of cultivation location in shaping the chemical characteristics of Z. officinale var. rubrum essential oil, providing valuable insights for developing tailored essential oil-based products to meet specific industrial requirements.